Brucellosis in sheep and goats in central Ethiopia - Tekelye Bekele; Kasali, O.B. (1990)
Serum samples collected from 1507 sheep and 1197 goats at Addis Ababa abattoir, Debre Berhan and Abomessa were tested for brucellosis using the Rose Bengal test. The overall prevalence rateswere 1.5 and 1.3 percent in sheep and goats respectively. Vaccinationwith strain Re1 is suggested as the possible means of control of brucellosis in small ruminants.